Efektifitas Perlindungan Konsumen Di Era Otonomi Daerah - Moh Issamsudin (UNISSULA Semarang, 2020)
AbstrakPemerintah memberlakukan Undang-undang Nomor 8 Tahun 1999 tentang Undang-undang Perlindungan Konsumen (UUPK) guna mewujudkan kegiatan perdagangan yang lebih baik, melindungi, dan meningkatka harkat serta martabat konsumen.Sekarang ini UUPK tidak dapat diwujudkan optimal ketika kewenangan Pemerintah Kabupaten/Kota di bidang perlindungan konsumen, dicabut setelah diberlakukannya Undang-undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah. Kewenangan itu sekarang hanya ada di Pemerintah Provinsi. Padahal Pemerintah Kabupaten/Kota memiliki tanggung jawab untuk menghormati dan memberi perlindungan pada konsumen serta mewujudkan perdagangan yang baik di daerahnya.Seperti di Kota Semarang, kegiatan perlindungan konsumennya sekarang ini sangat tidak efektif. Perlindungan konsumen yang ada semata-mata karena kebijakan. Sangat tepat bila Pemerintah Kabupaten/ Kota harus diberi lagi kewenangan di bidang perlindungan konsumen. Perlindungan itu penting karena menyangkut kebutuhan masyarakat dan harus dioptimalkan.Kata Kunci : Efektifitas, Perlindungan Konsumen, otonomi daerah AbstractIt is right if the government enacts Law No. 8 Year 1999 on Consumer Protection Law (UUPK) in order to realize better trade activities. Trading has to ensure the improvement of the public welfare and certainty of the quality, quantity, security of goods and/or services obtained by consumers. Consumers’ pride and dignity must always be improved.It is inappropriate if the good objectives of UUPK cannot be realized optimally when the authority of government(City/District) in the field of consumer protection is revocated after the enactment of Law Number 23 Year 2014 on Regional Government. Now, the authority exists only in the Provincial Government. Whereas the District orCity Government has the responsibility to respect and provide protection to consumers and to realize a good and right trade in the region.As happens as in Semarang, theconsumer protection activity is ineffective, passive and only active if it is invited by Provincial Government. Infact, the activities by the Provincial Government itself are very limited and must be given to 34 districts or other cities in Central Java.With the principle of the enforcement of UUPK is muchmore important than the authority revocation, Semarang City Government keeps trying to provide the best service for consumerprotection even with all kinds of its limitations. That is why it is very proper if once more, Semarang(District/City Government is given the authority in the field of consumer protection. Protection is important because it relates to the needs of the community and it must be optimized.Keywords: Effectiveness, Consumer Protection, regional autonomy